Association of night-waking and inattention/hyperactivity symptoms trajectories in preschool-aged children. Issue 1 (December 2018) - Reynaud, Eve; Forhan, Anne; Heude, Barbara; Charles, Marie-Aline; Plancoulaine, Sabine
Abstract The objective was to study the longitudinal associations between inattention/hyperactivity symptoms and night-waking in preschool-years, in light of their joint evolution. Within the French birth-cohort study EDEN, repeated measures of 1342 children's night-waking and inattention/hyperactivity symptoms were collected at age 2, 3 and 5–6 through questionnaires. Trajectories were computed using group-based modeling. Logistic regressions, adjusted for confounding factors, were used to measure the association between trajectories and to determine risk factors for belonging to the identified joint trajectories. Two night-waking trajectories were observed, 20% of the children had a trajectory of "common night-waking", and 80% a trajectory of "rare night-waking". The children were distributed in three inattention/hyperactivity trajectories, a low (47%), medium (40%) and high one (13%). Both night-waking and inattention/hyperactivity trajectories showed persistence of difficulties in preschool years. The risk of presenting a high inattention/hyperactivity trajectory compared to a low one was of 4.19[2.68–6.53] for common night-wakers, compared to rare night-wakers. Factors associated with joint trajectories were parent's education level and history of childhood behavioral problems, and the child's gender, night-sleep duration and collective care at 2 years of age. Results suggest that children presenting behavioral difficulties would benefit from a systematic investigation of their sleep quality and conversely.